Evaluation of the intergranular corrosion in austenitic stainless steel using collinear wave mixing method. (January 2015) - Jingpin, Jiao; Junjun, Sun; Guanghai, Li; Bin, Wu; Cunfu, He
Abstract: Failures due to intergranular corrosion in components of austenitic stainless steel have always been a tough problem in engineering practice. In this paper, the collinear wave mixing was investigated to evaluate the intergranular corrosion in austenitic stainless steel. An acoustic nonlinearity parameter related to the bispectrum, the propagation distance and the amplitudes of fundamental waves in measured signal is proposed. Nonlinear acoustic measurements were conducted on four tubes with different degree of intergranular corrosion. The experimental results demonstrated that the proposed acoustic nonlinearity parameter is sensitive to intergranular corrosion in samples, and is well correlated with the degree of damage. Highlights: A new acoustic nonlinearity parameter is introduced for detection of micro damage. The measurement is conducted using the collinear wave mixing technique associated with bispectral analysis. The proposed acoustic nonlinearity parameter is sensitive to intergranular corrosion in specimens. The measurement is not affected by system nonlinearities.